Agricultural policy in the European Union: An overview - Stefan Tangermann; Stephan von Cramon-Taubadel (Georg-August-Universität Göttingen, Department für Agrarökonomie und Rurale Entwicklung (DARE), 2013)
[Conclusions] All policy making, including for the agricultural sector, is of idiosyncratic nature and differs widely from country to country. However, due to its supra-national dimension the EU's Common Agricultural Policy is a very special case that is in no way even vaguely comparable to the agricultural policy regime in any other part of the world. The specificity of the CAP relates to several factors, including the historical origin, the process of decision making, the financing regime, and the global significance of the EU's agricultural sector. [...]
Keywords: 330